Back Cover: Impact of the Diazonium Grafting Control on the Interfacial Reactivity: Monolayer versus Multilayer (ChemElectroChem 2/2017). Issue 2 (23rd January 2017) - Menanteau, Thibaud; Dabos‐Seignon, Sylvie; Levillain, Eric; Breton, Tony
Abstract : The Back Cover picture illustrates a simple strategy to prepare versatile monolayer platform for "on surface" chemistry on carbon. This grafting method allows the electrochemical properties and interfacial reactivity of functional surfaces to be enhanced. More information can be found in the Communication by T. Breton and co‐workers onpage 278 in Issue 2, 2017 (DOI:10.1002/celc.201600710 ).